Anwā’u at-Tasybīh al-Mustakhdimah fī Riwāyati “Sunūnuwāt Kābūl” li Yāsmina Khadhrā - Rahmi, Hafizatur; Yunaldi, Yunaldi; Mustofa, Bisri (Universitas Negeri Malang, 2023)
Research on the style of balaghah language has a very important goal, which is to convey the beauty of the style of language conveyed by the author in a prose to convey the intended meaning to the readers, especially in the novel Sununuwati Kabul by Yasmina Khadra. This research needs to be discussed because after the researcher conducted a survey of this novel and the researcher found the beautiful Arabic styles that the author used in expressing an event that will be described to the reader, especially the Tashbih language style in Balaghah. So, with the explanation of this novel must be examined more deeply about the various styles of Tasybih language used by the author. The author of the novel Sununuwati Kabul uses tasybih language style in conveying ideas and goals. In this study, the researcher used a type of qualitative research, in which this research was more about describing or explaining the existing data, for the research method, the researcher used a descriptive analysis method. This method is carried out by explaining or describing the data then followed by an analysis of the data using a predetermined theory. As for data collection techniques, researchers used the library research method or library research to explain the data in this study. The results of this study are 7 types, including: tasybih mursal is totaling 4, tasybih mursal mufassal goiru tamtsil is totaling 28, tasybih mursyal mujmal is totaling 25, tasybih mursal mujmal jama' is totaling 1, tasybih muakkad mufassal goiru tamtsil is totaling 3, tasybih balig is totaling 2, tasybih mursal maqlub is totaling 5. And from these results the author concludes that this novel describes a beautiful and meaningful Arabic style. Because the style of tasybih language is not only one or two but, the author came up with many styles of tasybih language to express the parables of the parables of the existing events. هذا البحث عن أسلوب لغة البلاغة له هدف مهم للغاية، وهو نقل جمال أسلوب اللغة الذي ينقله المؤلف في نثر لإيصال المعنى المقصود للقراء، خاصة في رواية سنونوات الكابول لياسمينة خضرا. يستخدم مؤلف رواية سنونوات الكابول أسلوب لغة تشبيه في نقل الأفكار والأهداف. في هذه الدراسة، استخدم الباحث نوعًا من البحث النوعي، حيث كان هذا البحث أكثر حول وصف أو شرح البيانات الموجودة، أما بالنسبة لمنهج البحث، فقد استخدم الباحث أسلوب التحليل الوصفي. يتم تنفيذ هذه الطريقة من خلال شرح أو وصف البيانات ثم يتبعها تحليل البيانات باستخدام نظرية محددة سلفًا. أما بالنسبة لتقنيات جمع البيانات ، فقد استخدم الباحثون أسلوب البحث في المكتبات أو البحث المكتبي لشرح البيانات في هذه الدراسة. أما نتائج هذه الدراسة هي 7 أنواع ، بما في ذلك:تشبيه مرسل هو 4 ،تشبيه مرسل مفصل غير التمثيل هو 28 تشبيه مرسل مجمل هو 25، تشبيه مرسل مجمل جمع 'هو إجمالي 1 ،تشبيه مؤكد مفصل تمثيل هو 4، تسيبية بليغ هو 2 ، تشيبية مرسل مقلوب هو 5. ومن هذه النتائج يستنتج المؤلف أن هذه الرواية تصف أسلوبا عربيا جميلا وهادفا. لأن أسلوب لغة التشبيه ليس واحدا أو اثنين فقط ، ولكن المؤلف توصل إلى العديد من أنماط لغة التشبيه للتعبير عن أمثال الأحداث القائمة.